The Quranic Inferences of Druze - Al-Majali, Mohammad; Musa al-Aqtash, Bushra (Jurnal Usuluddin, 2024)
This paper discusses the status of the Druze towards the Qur’an, their esoteric interpretations and inferences, which affected their thought and belief, where the main question arose: What are the main Quranic interpretations and inferences of the Druze sect? The paper aims at studying the principles of the Druze sect and their ideas based on them, highlighting their status of the holy Qur’an, and criticizing the Quranic inferences of the Druze with regard to legal rulings. To fulfill this study we followed descriptive, analytical, and critical approaches. The paper concluded that the Druze have their own interpretation of the Quran, sometimes they oppose its clear meaning, they infer the Holy Qur’an in order to utilize it to promote their theological thoughts and legitimize them. It is remarkable that their private books (of their imams) are not public; this confirms the obscurity of this group in their beliefs, principles and opinions.